Pharmacokinetics, Tissue Localization, Toxicity, and Treatment Efficacy in the First Small Animal (Rabbit) Model of Intra-Arterial Chemotherapy for Retinoblastoma - Daniels, Anthony B.; Froehler, Michael T.; Pierce, Janene M.; Nunnally, Amy H.; Calcutt, M. Wade; Bridges, Thomas M.; LaNeve, David C.; Williams, Phillip E.; Boyd, Kelli L.; Reyzer, Michelle L.; Lindsley, Craig W.; Friedman, Debra L.; et al. (Investigative ophthalmology & visual science, 2018)
Current intra-arterial chemotherapy (IAC) drug regimens for retinoblastoma have ocular and vascular toxicities. No small-animal model of IAC exists to test drug efficacy and toxicity in vivo for IAC drug discovery. The purpose of this study was to develop a small-animal model of IAC and to analyze the ocular tissue penetration, distribution, pharmacokinetics, and treatment efficacy. Following selective ophthalmic artery (OA) catheterization, melphalan (0.4 to 1.2 mg/kg) was injected. For pharmacokinetic studies, rabbits were euthanized at 0.5, 1, 2, 4, or 6 hours following intra-OA infusion. Drug levels were determined in vitreous, retina, and blood by liquid chromatography tandem mass spectrometry. To assess toxicity, angiograms, photography, fluorescein angiography, and histopathology were performed. For in situ tissue drug distribution, matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI-IMS) was performed. The tumor model was created by combined subretinal/intravitreal injection of human WERI-Rb1 retinoblastoma cells; the tumor was treated in vivo with intra-arterial melphalan or saline; and induction of tumor death was measured by cleaved caspase-3 activity. OA was selectively catheterized for 79 of 79 (100%) eyes in 47 of 47 (100%) rabbits, and melphalan was delivered successfully in 31 of 31 (100%) eyes, without evidence of vascular occlusion or retinal damage. For treated eyes, maximum concentration (Cmax) in the retina was 4.95 μM and area under the curve (AUC0→∞) was 5.26 μM·h. Treated eye vitreous Cmax was 2.24 μM and AUC0→∞ was 4.19 μM·h. Vitreous Cmax for the treated eye was >100-fold higher than for the untreated eye (P = 0.01), and AUC0→∞ was ∼50-fold higher (P = 0.01). Histology-directed MALDI-IMS revealed highest drug localization within the retina. Peripheral blood Cmax was 1.04 μM and AUC0→∞ was 2.07 μM·h. Combined subretinal/intravitreal injection of human retinoblastoma cells led to intra-retinal tumors and subretinal/vitreous seeds, which could be effectively killed in vivo with intra-arterial melphalan. This first small-animal model of IAC has excellent vitreous and retinal tissue drug penetration, achieving levels sufficient to kill human retinoblastoma cells, facilitating future IAC drug discovery.